2006
DOI: 10.1634/stemcells.2005-0416
|View full text |Cite
|
Sign up to set email alerts
|

Nucleostemin Is a Marker of Proliferating Stromal Stem Cells in Adult Human Bone Marrow

Abstract: When bone marrow stem cells were differentiated into chondrocytes, adipocytes, or osteocytes, nucleostemin expression was 70%-90% lower than in the undifferentiated cells retained in monolayer culture. We conclude that nucleostemin is a marker of undifferentiated human adult bone marrow stem cells and that it is involved in the regulation of proliferation of these cells. STEM CELLS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 35 publications
7
94
2
Order By: Relevance
“…Besides the bone marrow, adult stem cells have been isolated from a variety of tissues, such as the liver, nerve, muscle, skin, synovium and cartilage. 33,34 Recent studies have shown that extracted non-decayed impacted third molar tooth germ tissues could serve as a very valuable source of stem cells. As these tissues are removed during standard prophylactic interventions and do not require additional surgical procedures, utilization of such resources to isolate stem cells offers an attractive alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the bone marrow, adult stem cells have been isolated from a variety of tissues, such as the liver, nerve, muscle, skin, synovium and cartilage. 33,34 Recent studies have shown that extracted non-decayed impacted third molar tooth germ tissues could serve as a very valuable source of stem cells. As these tissues are removed during standard prophylactic interventions and do not require additional surgical procedures, utilization of such resources to isolate stem cells offers an attractive alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR analysis revealed that hTGSCs present undifferentiated cell markers such as nucleo-stemin and human telomerase reverse-transcriptase, indicating that these cells are in an undifferentiated, proliferative state. 34 Although hTGSCs were proliferative, the expression of oct4 decreased gradually as the passage number increased. As oct4 is crucial for the maintenance of the pluri-potency, 35 decrease in oct4 in subsequent passages might indicate the loss of differentiation capacity of hTGSCs and potential senescence.…”
Section: Figurementioning
confidence: 99%
“…High levels of nucleostemin expression are also detected in several types of cancer cells [16][17][18]. Although the role of nucleostemin in U2OS human osteosarcoma cells has been assessed extensively by siRNA-mediated knockdown experiments, the physiological function of nucleostemin in stem cells has been little characterized, with the exception of a few studies [15,45]. Here, we assessed the roles of nucleostemin in ES cells and ES cell-derived neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is generally assumed that nucleostemin plays an important role in stem cell proliferation. However, with the exception of a few studies using stromal stem cells from adult human bone marrow [15], most studies investigating nucleostemin function have been performed using nonstem cells, such as U2OS osteosarcoma cells [16][17][18]. The role of nucleostemin in stem cells is therefore still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of expression of these pluripotency markers in intact patellar tendon suggested that immunohistochemical staining of these markers was not suitable for the detection of tendon stem cell in intact tendon in situ. The activation of Oct4, Nanog, Sox2, and nucleostemin as well as CD146 after tendon injury might be related to the functions of these proteins in regulating self-renewal, cell proliferation, differentiation, and/or angiogenesis [28][29][30][31][32].…”
Section: Role Of Lrcs During Tendon Repairmentioning
confidence: 99%